SIMULASI PENGARUH PENGGUNAAN FILTER CHEBYSHEV TIPE II PADA MASUKAN SINYAL GETARAN ACAK TERHADAP NILAI RATA-RATA MAGNITUDO - Henci Smartenlike Lokollo; Jotje Rantung; Michael Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
Filter in this research is interpreted as screening of undesirable frequency component in order to depressed it as small as possible to produce the changes of magnitude of response signal. The filtered vibration signal is in a form of the Random Signal Excitation which is generated in MATLAB Version 6.5. The signal is filtered by using Filter Chebyshev Type II. Simulation conducted repeatedly from 10 to 100 times excitation. Magnitude of Response Filter is obtained after simulation. Result is compared to its initial and expressed in the form of different percentage of magnitude between the mean of Magnitude of Response Filter because of applying Random Excitation Signal to the Excitation of Signal Impact from 10 to 100 times. Maximum different percentage of highest magnitude occurred in the simulation of 10 times excitation (57%). While the Minimum occurred in the simulation of 50 times (32%). Keyword : Filter Chebyshev of Type II, Random Excitation, Different Percentage Magnitude.